Differential profiles of salivary proteins with affinity to Streptococcus mutans lipoteichoic acid in caries‐free and caries‐positive human subjects. (28th July 2014) - Hong, S.W.; Seo, D.‐G.; Baik, J.E.; Cho, K.; Yun, C.‐H.; Han, S.H.
Summary Streptococcus mutans is a representative oral pathogen that causes dental caries and pulpal inflammation. Its lipoteichoic acid (Sm.LTA) is known to be an important cell‐wall virulence factor involved in bacterial adhesion and induction of inflammation. Since Sm.LTA‐binding proteins (Sm.LTA‐BPs) might play an important role in pathogenesis and host immunity, we identified the Sm.LTA‐BPs in the saliva of caries‐free and caries‐positive human subjects using Sm.LTA‐conjugated beads and LTQ‐Orbitrap hybrid Fourier transform mass spectrometry. Sm.LTA was conjugated to N‐hydroxysuccinimidyl‐Sepharose® 4 Fast Flow beads (Sm.LTA‐beads). Sm.LTA retained its biological properties during conjugation, as determined by the expression of nitric oxide and interferon‐γ‐inducible protein 10 in a murine macrophage cell line and activation of Toll‐like receptor 2 (TLR2) in CHO/CD14/TLR2 cells. Sm.LTA‐BPs were isolated from pooled saliva prepared from 10 caries‐free or caries‐positive human subjects each, electrophoresed to see their differential expression in each group, and further identified by high‐resolution mass spectrometry. A total of 8 and 12 Sm.LTA‐BPs were identified with statistical significance in the pooled saliva from the caries‐free and caries‐positive human subjects, respectively. Unique Sm.LTA‐BPs found in caries‐free saliva included histone H4, profilin‐1 and neutrophil defensin‐1, and those in caries‐positive saliva included cystatin‐C, cystatin‐SN, cystatin‐S, cystatin‐D, lysozyme C, calmodulin‐like protein 3 and β‐actin. The Sm.LTA‐BPs found in both groups were hemoglobin subunits α and β, prolactin‐inducible protein, protein S100‐A9, and SPLUNC2. Collectively, we identified Sm.LTA‐BPs in the saliva of caries‐free and caries‐positive subjects, which exhibit differential protein profiles.